ANALYSIS ON PERCEPTION OF LAND CONSOLIDATION PROJECTS IN BANTUL, SLEMAN, AND GIANYAR REGENCIES, INDONESIA - , Walidi; , Prof. Ir. Bakti Setiawan, MA, Ph.D, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Land consolidation (LC) project is one way to address land issues caused by an increasing population in Indonesia. One of the key successes of implementation of the LC project is landowner participation. This research investigates the different landowner characteristics, to explore landowner participation and the level of successfulness for the LC project, learn the correlation between landowner attributes, participation and successfulness of LC project, and find a promotion method for both participation and successfulness for the LC project in Bantul, Sleman, and Gianyar Regencies, Indonesia. A questionnaire of 45 landowners was conducted at each LC project site, containing 11 questions about landowner attributes, 10 questions about landowner participation and 11 questions about successfulness of the LC project. A total of 135 samples (45 x three sites) were obtained through random sampling. The results were analyzed using descriptive analysis, Spearman Rank Correlation Test, Kruskal Wallis Test, Simple Linear Regression Analysis and Multiple Linear Regression Analysis. Correlation between level of landowner participation and level of successfulness in all three locations had a strong, positive and significant correlation. Factors / variables that affected the level of landownersâ participation varied for each site. These factors need to be controlled by governments/executors to increase landowner participation level at each LC project site and increase successfulness of LC projects related to level of landownersâ participation level. If participation be raised by 1 point, the level of success will rise by 0.375 (Bantul), 0.464 (Sleman) and 0.842 (Gianyar).